The Association of Cell Surface Fibromodulin Expression and Bladder Carcinoma: Anti-FMOD induce apoptosis in bladder cancer - Bayat, Ali-Ahmad; Sadeghi, Niloufar; Salimi, Ali; Fazli, Ghazaleh; Nowroozi, Mohammad Reza; Ohadian Moghadam, Solmaz; Radmanesh, Amin; Tabasi, Mohsen; Sarrafzadeh, Ali Reza; Zarei, Omid; Rabbani, Hodjattallah (Urology Journal, 2021)
Background: Fibromodulin (FMOD) is a secretory protein which is considered a major component of extracellular matrix. Its dysregulation in different types of cancer implies it as a promising target for cancer therapy. Within the scope of its rather wide expression in different tumors, we studied expression of FMOD and effect of anti-FMOD antibody in bladder cancer cells in order to identify new target for diagnostic and therapeutic interventions. We report here for the first time the expression of FMOD in bladder cancer cell lines in comparison to the normal cell line and tissues. Methods: A peptide-based produced anti-FMOD murine monoclonal antibody (mAb) (clone 2C2-A1) was applied for evaluation of FMOD expression in bladder cancer and normal tissues by immunohistochemistry (IHC) staining. Furthermore, the expression of FMOD was examined in human bladder cell lines, 5637 and EJ138, as well as a non-cancerous human cell line, human fetal foreskin fibroblast (HFFF), by immunocytochemistry (ICC) and flow cytometry. The apoptosis induction of anti-FMOD mAb was also evaluated in bladder cancer cells. Results: IHC and ICC analyses revealed that the qualitative expression of FMOD in bladder cancer tissues and cell lines is higher than in normal tissues and cell lines. Flow cytometry analyses revealed that 2C2-A1 mAb could recognize FMOD expression in 84.05 ± 1.85%, 46.1 ± .4% , and 2.56 ± 1.26% of 5637, EJ138, and HFFF cells, respectively. An effective apoptosis induction was detected in 5637 and EJ138 cells with no significant effect on HFFF cell. Conclusion: To our knowledge, this is for the first time reporting surface expression of FMOD in bladder cancer. This significant surface expression of FMOD in bladder cancer with no expression in normal bladder tissues and the capacity of inducing apoptosis through directed targeting of FMOD with specific monoclonal antibody might candidates FMOD as a diagnostic marker as well as a potential immunotargeting with monoclonal antibody.